Religion and culture - Dawson, Christopher, 1889-1970 (Dawson, Christopher, 1889-1970. Works. 2001., 2013)
This book was first presented by historian Christopher Dawson as part of the prestigious Gifford Lecture series in 1947. It sets out the thesis for which he became famous: religion is the key of history.